Characteristic of the epidemiology of leptospirosis at the present stage - O. L. Pavlenko (Zaporožskij Medicinskij Žurnal)
Introduction. Studying changes in the epidemic process of leptospirosis in modern condition become topical. Prevention efforts must be developed with consideration with the global trends and regional peculiarities, as well as the stability of epizootic processes in nature.